Daya Terima Siomay dengan Substitusi Ikan Gabus dan Penambahan Daun Kelor sebagai Snack Tinggi Albumin dan Zat Besi - Iif Fitriyatul Mahmudah; Asrul Bahar (Jurnal Ilmu Kesehatan dan Gizi, 2025)
A new snack innovation that is high in albumin and iron content in the form of dumplings uses snakehead fish substitution and the addition of Moringa leaves. The aim of this research was to determine the effect of snakehead fish substitution, the addition of Moringa leaves, the interaction of the two factors on the acceptability of dumplings (color, aroma, taste, texture), as well as the best albumin and iron content of dumplings. This research used an experimental method with a 3x2 factorial design which resulted in 6 treatments. The data collection technique uses a sensory test based on the liking level of 50 untrained panelists. The results of the sensory test data were analyzed using the Two Way Anova Test followed by the Duncan Test to determine significant differences in results, as well as to determine the best dumplings. Based on the results, the acceptability of dumplings only had an effect on texture, and had no effect on color, aroma, taste, either from the substitution of snakehead fish or the addition of Moringa leaves, while the interaction between snakehead fish substitution and the addition of Moringa leaves had no effect on color, aroma, taste and texture. The best dumplings are snakehead fish (100%) and Moringa leaves (20%) with a nutritional value of 4.10 mg albumin and 2.10 mg iron per 100 grams. The conclusion of this research is that substitute snakehead fish dumplings and the addition of Moringa leaves only affect the texture, however, the dumplings can still be consumed by the panelists and are useful for increasing albumin levels and body endurance as well as speeding up wound healing.